The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.20286/jech-010458
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting Behaviors in Pregnant Women Admitted to the Prenatal Care Unit of Imam Khomeini Hospital of Saqqez

Abstract: Background and Objectives: Health promoting behaviors are crucial to the health of pregnant women and their children. The present study was conducted to assess health promoting behaviors in pregnant women admitted to Imam Khomeini Hospital of Saqqez. Materials and Methods: The present descriptive analytical study was conducted on 181 pregnant women selected through convenience sampling. The data collection tool used in the study was a questionnaire containing two parts: a section on the subjects' demographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…Only the studies conducted in Thailand by Thaewpia and colleagues as well as Onat in turkey reported a better total score (24,25). The results of the study indicated that the overall scores of behaviors were average; high scores were related to the dimension of spiritual growth (self-actualization) and nutritional status; scores related to social support and accountability were average; and the lowest score was related to stress management and physical activity (9). A review on foreign studies indicated that pregnant women had gained high scores in dimensions of self-actualization, social support, and accountability; average scores in nutrition; and low scores in stress management and physical activity (5,11,16).…”
Section: Observational Studiesmentioning
confidence: 96%
See 4 more Smart Citations
“…Only the studies conducted in Thailand by Thaewpia and colleagues as well as Onat in turkey reported a better total score (24,25). The results of the study indicated that the overall scores of behaviors were average; high scores were related to the dimension of spiritual growth (self-actualization) and nutritional status; scores related to social support and accountability were average; and the lowest score was related to stress management and physical activity (9). A review on foreign studies indicated that pregnant women had gained high scores in dimensions of self-actualization, social support, and accountability; average scores in nutrition; and low scores in stress management and physical activity (5,11,16).…”
Section: Observational Studiesmentioning
confidence: 96%
“…Income and job status of individuals were other factors under the study indicating the negative effects of poverty on healthcare behaviors (23). Moreover, employed people with high incomes had higher scores in health-promoting behaviors (2,9,26), especially in terms of self-actualization, responsibility, physical activity and nutrition (9,16,24). According to a study conducted by Esperat et al in the United States, marital status was a predictor of healthcare behaviors in such a way that single people received less support and faced problems regarding health-promoting behaviors (23).…”
Section: Observational Studiesmentioning
confidence: 99%
See 3 more Smart Citations